One-stage prepectoral reconstruction with "heavy" polypropylene mesh implant support in breast cancer surgery - D. N. Rovenskikh; S. A. Usov (ABV-press, 2023)
Background. One-stage prepectoral implant-based reconstruction (OSPIBR) using biocompatible synthetic meshes support gained wide popularity in breast cancer surgery. Optimal structure of polypropylene mesh implants (PMI) and methods of its application are actively discussed.Aim. To study the effectiveness and safety of prosthesis support with "heavy" PMI in OSPIBR. Materials and methods. During 2019-2021 18 OSPIBR with "heavy" PMI support were performed after subcutaneous mastectomies in 14 patients. Cancer was indication for surgery in 13 cases (two of them - with BRCA1 mutation) and BRCA1 mutation solely - in 1 case. Foamed polyurethane covered silicone prosthesis (Polytech, Germany) was used for OSPIBR and "heavy" PMI PROLENE™ Polypropylene Mesh (Ethicon/Johnson & Johnson, USA) for prosthesis support by original method.Results. The overall complication rate was 5.6 % (1/18). It was a minor complication: limited aseptic skin necrosis along incision edge, successfully excised under local anesthesia. No cancer recurrences or capsular contracture formation were registrated during follow-up (6 months). The cosmetic outcome (Harvard score) was excellent in 11 of them and good in 3.Conclusions. "Heavy" PMI application by original technique in OSPIBR after subcutaneous mastectomy for breast cancer is a safe and effective method of prosthesis support.